Between Enabling Law and Protecting Law – Some Remarks on the Method of Regulating the Law of Groups of Companies in Polish Commercial Companies Code - Herbet, Andrzej (Review of European and Comparative Law, 2023)
Although the groups of companies have been an indispensable part of the modern economy for several decades, they still continue to attract unwavering attention of both practice and doctrine of corporate law. The numerous legal challenges posed by the functioning of multi-level structures, based on diverse types of dominance and dependance relations adopt different regulatory strategies manifest a universal appeal. Yet, the national legislators adopt different regulatory strategies, aimed at securing the interests of various stakeholders, including minority shareholders, dependent companies and their creditors. As a result, the contemporary discourse entails two concepts – one emphasizing the risks and responsibilities associated with it (protecting law) and the other one, supporting the creation of groups, as well as instruments for their effective management (enabling law). The aim of the article is to verify the extent to which these concepts are addressed by the most recent Polish group law regulations, viewed in a comparative context outlined by selected European jurisdictions.